ANALISIS PENGHEMATAN DAN KONSERVASI ENERGI DI GEDUNG PERKANTORAN - Asmi, M. Fariz Dwi; Aini, Zulfatri (Rang Teknik Journal, 2026)
The use of electrical energy in buildings has the potential to cause wastage of electrical energy, such as lighting, lighting, electronic devices and equipment installed that does not comply with standards. This research aims to obtain building standardization by calculating the Energy Consumption Intensity (IKE) value, making savings on air and lighting systems, and calculating energy consumption costs. The savings that can be made in this research are savings by implementing energy conservation through technological improvement methods in lighting and air conditioning systems. On the procedures for implementing other savings by implementing energy saving behavior. Then calculate consumption costs using the financial assessment stages. Based on an audit of electrical energy in this office building, the IKE value obtained was 78.08 kWh per year. This value is considered efficient for office buildings. However, several conditions were found that caused energy waste, such as the use of fluorescent fluorescent lamps in the lighting system. The use of these lamps tends to be wasteful so they need to be replaced with LED TL lamps. The savings obtained on lighting are 55%. And in the cooling system the AC capacity does not match the area per floor. The savings obtained from air conditioning are 15% with the resulting kWh value being 511.2 kWh from the previous savings of 677.7 kWh.Keywords: Electrical Energy Audit, Energy Conservation, Energy Consumption Intensity